2016
DOI: 10.1007/s00300-016-1926-x
|View full text |Cite
|
Sign up to set email alerts
|

Demography and ecology of southern right whales Eubalaena australis wintering at sub-Antarctic Campbell Island, New Zealand

Abstract: 1Since the decimation of the southern right whale Eubalaena australis population in New Zealand 2 by whaling, research on its recovery has focused on the wintering ground at the Auckland 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…Range expansion and recolonization to new areas has been observed for other SRW populations, such as Brazil (Groch et al 2005, Danilewicz et al 2016), Argentina (Arias et al 2017, Rowntree et al 2001, Uruguay (Costa et al 2005), South Africa (Best 1990, Barendse andBest 2014), and New Zealand (Carroll et al 2011(Carroll et al , 2014a and Campbell Islands (Torres et al 2016). These areas show evidence of recolonization into former areas around the main nursery area in association with population growth.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Range expansion and recolonization to new areas has been observed for other SRW populations, such as Brazil (Groch et al 2005, Danilewicz et al 2016), Argentina (Arias et al 2017, Rowntree et al 2001, Uruguay (Costa et al 2005), South Africa (Best 1990, Barendse andBest 2014), and New Zealand (Carroll et al 2011(Carroll et al , 2014a and Campbell Islands (Torres et al 2016). These areas show evidence of recolonization into former areas around the main nursery area in association with population growth.…”
Section: Discussionmentioning
confidence: 82%
“…, ) and Campbell Islands (Torres et al . ). These areas show evidence of recolonization into former areas around the main nursery area in association with population growth.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in distribution of different demographic classes have been linked with changes in density in multiple SRW populations. Increases in the number of cow-calf pairs displaces social groups and solitary individuals to other habitat in Argentina (Rowntree, 2001;Arias et al, 2018) New Zealand (Carroll et al, 2014Torres et al, 2017), and Australia (Charlton, 2017).…”
Section: Factors Driving Distributionmentioning
confidence: 99%
“…The SRW are circumpolar in the Southern Hemisphere between about 12 • S and 65 • S, albeit with a large historical and contemporary discontinuation between New Zealand and Chile. The austral winter distribution of SRW (Figure 1) includes the New Zealand sub-Antarctic Auckland and Campbell Islands (Carroll et al, 2013;Torres et al, 2017), with far fewer whales reported around mainland New Zealand (Carroll et al, 2014). In Australian coastal waters, SRW occur along the southern coastline including Tasmania, generally as far north as Sydney on the east coast and Perth on the west coast (Carroll et al, 2011).…”
Section: Srwmentioning
confidence: 99%
See 1 more Smart Citation